Quantitative Disease Resistance to White Pine Blister Rust at Southwestern White Pine’s (Pinus strobiformis) Northern Range - Johnson, Jeremy S.; Sniezko, Richard A. (Frontiers in Forests and Global Change, 2021)
White pine blister rust, caused by the non-native, invasive fungal pathogen Cronartium ribicola, is a significant cause of mortality in white pines (Pinus subgenus Strobus) in North America. Along with climate-driven range contraction, mortality from blister rust can seriously impact the abundance and distribution of the nine white pine species native to the United States and Canada. Very little evaluation of this disease in southwestern white pine (Pinus strobifomis) has been previously undertaken, but genetic resistance to the disease has been documented, including major gene resistance (MGR) conferred by a dominant R gene. Data is emerging suggesting that the species also has quantitative disease resistance (QR). Our results suggest QR occurs at low frequency, with perhaps 10% of trees having a moderate level (>35% survival). We assess progeny arrays from 40 P. strobiformis families (1873 seedlings), originating from three populations, inoculated with C. ribicola. Subsequently, the seedlings were assessed for signs, symptoms and resulting impact in a common garden trial over a 7.5-year period to determine the types and frequency of resistance in a portion of this species’ range. There was a high incidence of both stem symptoms and mortality in the P. strobiformis families tested, and families ranged in survival from 0 to 84.6%. Three families had >70% survival, representing perhaps the highest documented QR to date in a North American white pine species. Approximately 7% of surviving seedlings showed no stem symptoms, with approximately 16% of seedlings surviving with infections of generally low severity. QR traits associated with improved survival were primarily related to lower severity of infection, a reduced number of stem symptoms, and an increased number of bark reactions. Despite the high overall susceptibility, the presence of QR appears to be at a frequency and level useful to forest managers involved in restoration and reforestation efforts.